A Comprehensive Characterization of Biochar Derived from Grape Pomace via Fast Pyrolysis - Turkan Aktas; I. Savas Dalmis; Levent Taseri; Tolga Batur (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The effects of pyrolysis temperature and heating rate on yield and quality properties of biochar obtained from grape pomace were investigated. Surface properties and heat values were determined in addition to proximate and elemental analyses. Experiments were made at the conditions of 400, 500 and 600 °C pyrolysis temperature and 200, 400 and 600 C/min heating rate. Increase of pyrolysis temperature and heating rate decreased the biochar yield. There was a general decrease in the moisture values of the biochar samples and an increase in the ash content with increasing of pyrolysis temperature. Heating value, fixed carbon content and volatile matter content of the biochar samples changed between 24.92-28.62 MJ/kg, 60.18-74.02%, and 8.59-28.97%, respectively. Elemental analyses results showed that contents of C, H, O, N were determined between 71.23-80.34%, 2.80-5.06%, 0-12.9%, and 2.04-2.93%, respectively. SEM images of raw material namely grape pomace and biochar samples showed that increase in the number of pores occurred with the pyrolysis process.
Keywords: Pyrolysis; Biochar Yield; SEM Image; Heat Value; Characterization